2019
DOI: 10.1111/iji.12418
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I allele lineages and haplotype frequencies in Arabs of the United Arab Emirates

Abstract: The high degree of polymorphism of the HLA system provides suitable genetic markers to study the diversity and migration of different world populations and is beneficial for forensic identification, anthropology, transplantation and disease associations. Although the United Arab Emirates (UAE) population of about nine million people is heterogeneous, information is limited for the HLA class I allele and haplotype frequencies of the Bedouin ethnic group. We performed low‐resolution PCR‐SSP genotyping of three H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…While the Japanese, north‐eastern Thai and several other Asian populations appear to share similar allele frequency distributions, a distinctly lower frequency of Alu insertions in the African sub‐Saharan subpopulations has given rise to a sparser topology on the phylogenetic tree (Figure ). The results from this study of Arabs from the United Arab Emirates are in accordance with the hypothesis that early humans originated in Africa, the Out of Africa hypothesis (Antunez‐de‐Mayolo et al, ), with the Middle East having acted as a crossroads from which populations then migrated east to Asia and to the north‐west to Europe (Kulski et al, ).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…While the Japanese, north‐eastern Thai and several other Asian populations appear to share similar allele frequency distributions, a distinctly lower frequency of Alu insertions in the African sub‐Saharan subpopulations has given rise to a sparser topology on the phylogenetic tree (Figure ). The results from this study of Arabs from the United Arab Emirates are in accordance with the hypothesis that early humans originated in Africa, the Out of Africa hypothesis (Antunez‐de‐Mayolo et al, ), with the Middle East having acted as a crossroads from which populations then migrated east to Asia and to the north‐west to Europe (Kulski et al, ).…”
Section: Resultssupporting
confidence: 89%
“…The percentage association and linkage disequilibrium (LD) values between the Alu insertions and HLA allelic lineages as two‐locus haplotypes in UAE Arabs were determined using the HLA allele lineages (Kulski et al, ) and the Alu allelic data reported here for the same samples. Supporting Information Table shows the alleles frequencies for HLA‐A, HLA ‐B and HLA ‐C and their percentage association with the 5 MHC class I POALIN frequencies in UAE Arab population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations